2008
DOI: 10.4321/s0213-61632008000400006
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence and impact of stalking: Epidemiological data from Eastern Austria

Abstract: -Background and Objectives: Community-based studies of stalking in European countries are scarce. The aim of the present study was to replicate the epidemiological study by Dressing and colleagues, which analyzed a sample drawn from a middle-sized German city (Dressing et al., 2005) by using a general population sample (urban as well as rural citizens) from Eastern Austria.Methods: In a survey of 401 persons from Eastern Austria we tried to replicate the study on the lifetime and point prevalence of stalking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 12 publications
3
34
0
6
Order By: Relevance
“…Although prevalence studies on stalking have used large scale representative community samples inside and outside of Europe (e.g., Stieger et al 2008;Tjaden and Thoennes 1998), the majority of UPB and stalking studies examining former partners have used non-European college student samples. However, Ravensberg and Miller's (2003) review illustrated that college students differ from the general adult population in their experiences of stalking.…”
Section: Methodological Limitations Of Previous Researchmentioning
confidence: 99%
“…Although prevalence studies on stalking have used large scale representative community samples inside and outside of Europe (e.g., Stieger et al 2008;Tjaden and Thoennes 1998), the majority of UPB and stalking studies examining former partners have used non-European college student samples. However, Ravensberg and Miller's (2003) review illustrated that college students differ from the general adult population in their experiences of stalking.…”
Section: Methodological Limitations Of Previous Researchmentioning
confidence: 99%
“…But the epidemiology of stalking has also been investigated in European countries (for example, Dovelius et al, 2006;FRA, 2014;Matos et al, 2012;Stieger et al, 2008;Van der Aa and Kunst, 2009). For Germany, no nationally representative data on the prevalence of stalking exist so far: Dressing, Kuehner, and Gass (2005) reported first estimates of the prevalence of stalking in Germany.…”
Section: Introductionmentioning
confidence: 96%
“…As UPB involves the full range of mild to severe unwanted pursuit tactics, it is more widespread than stalking and mostly aggravating or annoying but not fear-inducing (e.g., Cupach & Spitzberg, 1998. For instance, lifetime prevalence estimates of ex-partner stalking victimization in nationally representative studies amount to 3-4% (Dressing, Gass, & Keuhner, 2007;Purcell, Pathé, & Mullen, 2002;Stieger, Burger, & Schild, 2008) whereas in a recent representative study of adult ex-partners, 37% were found to have used at least one pursuit tactic after their breakup . In the latter study, most of the registered tactics were benign tactics (i.e., watching the ex-partner, monitoring the ex-partner, making exaggerated expressions of affection).…”
Section: Differencesmentioning
confidence: 99%